O gênero conto como interface para o letramento literário a partir do tema feminicídio - Soares, Sunamita da Silva (2020)
In order to increase the dissemination of literary reading and to provide to students the involvement with the literary text, the purpose of this research consists of the literary literacy proposed through the genre tale on the topic of feminicide. Besides that, in the research, a didactic proposal is presented, basing on the basic sequence of Rildo Cosson and the elements of Hans Kügler’s critical reading. The main objective of this work is to take students to critical reading and, consequently, to the literary literacy and to the underlying questions the texts related to feminicide. This proposal was developed in a class tantamount to an eighth grade class offered to adults that decided to resume their studies at Centro Educacional Incra 9, a rural school located in the satellite city of Ceilândia-DF. Bearing in mind that in order to achieve the objectives, it was necessary to work with the specificities of the genre tale, enhancing students’ reading and interpretation and providing opportunities for discussion about the texts read. It was also incited the dialogue between fictional texts and the historical and cultural context we liveby. Moreover, a reading diary was organized with the students during the application, which allowed us to observe their positions before the readings and whether the development of the proposal contributed to the construction of literary literacy. As a final product, a collective wall was created for them to express their critical positioning on the theme of femicide in line with the literary content that was proposed.